Highly Loaded Multi‐Walled Carbon Nanotubes Non‐Covalently Modified with a Bis‐Imidazolium Salt and their Use as Catalyst Supports. Issue 5 (5th April 2016) - Salvo, Anna Maria Pia; La Parola, Valeria; Liotta, Leonarda F.; Giacalone, Francesco; Gruttadauria, Michelangelo
Abstract: The surfaces of multi‐walled carbon nanotubes (MWCNTs) were non‐covalently modified using two bis‐imidazolium dibromide derivatives having phenyl or pyrene groups. Due to the presence of the two pyrene groups the bis(pyren‐1‐ylmethylimidazolium) dibromide derivative was immobilised at a loading of about 15–16 wt %, whereas only <3 wt % of the phenyl derivative was immobilised. The presence of the two imidazolium cations helped the immobilisation of tetrachloropalladate ions after exchange with bromide ions. Tetrachloropalladate was used as pre‐catalyst in several Suzuki–Miyaura carbon–carbon cross‐coupling reactions in water or water/ethanol at 50 °C in only 0.1 mol % and compared with the non‐supported pre‐catalyst. The MWCNT‐supported material was used in five consecutive cycles of the Suzuki–Miyaura reaction. Recycling using phenylboronic acid and 4‐bromobenzaldehyde in water/ethanol was achieved with only a minor loss in activity. HRTEM images clearly showed the presence of the bis(pyren‐1‐ylmethylimidazolium) derivative on the sidewalls of MWCNTs. Abstract : Two birds with one stone : A molecule has been synthesised with two pyrenyl and two imidazolium moieties, which anchored the catalyst tetrachloropalladate to multi‐walled carbon nanotubes with high loading. Such noncovalently modified materials could be used up to five times in the Suzuki–Miyaura reaction (see scheme).